Scepticism in CSR Advertisements - Farache, Francisca (HERMES - Journal of Language and Communication in Business, 2012)
The aim of the present paper is to make a contribution to CSR communication theory by investigating the level of substantial information provided in CSR print advertisements in the UK and Brazil. The paper evaluates CSR advertisements using textual analysis. The empirical evidence demonstrates that companies provide a low level of substantial information when advertising CSR. The paper provides empirical evidence as to the extent that corporations use substantial information in their advertisements.